MRI diffusion of rotator cuff muscle in two different type of training methods of state-level weightlifters - Sapiai, Nur Asma (2017)
Objective: To compare the rotator cuff muscles changes on MRI Diffusion study between state-level weightlifter who underwent fast isokinetic training (FIT) and traditional isotonic training (TOT) exercise. Methodology: Gender and weight matched subjects were grouped into two types of exercises; FIT and TOT. Both groups underwent 24 sessions of training consisted of 3 distinct lifting positions. The trainings were scheduled 3 times per week for 8 weeks. MRI diffusion was conducted twice, at pre-training and 1 week post-training completion. The Fractional anisotropy (FA), Apparent Diffusion Coefficient (ADC) values and eigenvalues between two groups were evaluated. Results: A total of 22 subjects were enrolled but only 16 subjects completed the training programmes. Equal number of subjects (n=8) were subjected for each training programme. There were significant changes of the λ1 in supraspinatous muscle (SSM), infraspinatous muscle (ISM) and subscapularis muscle (SCM) in FIT indicate increased in muscles elongation almost in similar pattern. FA values increased in both training methods for all the muscles except supraspinatous muscle (SSM) in TOT. Among these, only FA of Subscapularis muscle (SCM) in FIT was statistically significant. Conclusions: Both FIT and TOT have a potential to be proposed as an additional mode of training among the experienced weightlifters to improve their performance. DTI is a good technique to evaluate muscle diffusion changes.